2017
DOI: 10.2147/ijn.s133034
|View full text |Cite|
|
Sign up to set email alerts
|

Liposomal formulation of a methotrexate lipophilic prodrug: assessment in tumor cells and mouse T-cell leukemic lymphoma

Abstract: In a previous study, a formulation of methotrexate (MTX) incorporated in the lipid bilayer of 100-nm liposomes in the form of diglyceride ester (MTX-DG, lipophilic prodrug) was developed. In this study, first, the interactions of MTX-DG liposomes with various human and mouse tumor cell lines were studied using fluorescence techniques. The liposomes composed of egg phosphatidylcholine (PC)/yeast phosphatidylinositol/MTX-DG, 8:1:1 by mol, were labeled with fluorescent analogs of PC and MTX-DG. Carcinoma cells ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 38 publications
4
24
0
2
Order By: Relevance
“…The influence of the preparation method of liposomes was also evaluated using the remote loading. However, this approach can only be applied to weak amphipathic acids or bases, which MTX molecule does not belong to Alekseeva et al (2017). Liposomes encapsulating DOX, prepared by remote loading, was then used in this study, however, high leakage level is also observed (24.5%, Table 2).…”
Section: Influence Of the Freeze-drying On Drug Leakage From Liposomesmentioning
confidence: 99%
“…The influence of the preparation method of liposomes was also evaluated using the remote loading. However, this approach can only be applied to weak amphipathic acids or bases, which MTX molecule does not belong to Alekseeva et al (2017). Liposomes encapsulating DOX, prepared by remote loading, was then used in this study, however, high leakage level is also observed (24.5%, Table 2).…”
Section: Influence Of the Freeze-drying On Drug Leakage From Liposomesmentioning
confidence: 99%
“…AUC ratios of various L-LDCs. [34 ], [39] , [10] , [25] , [40] , [32], [41] , [42] , [38] , [43] , [44], [45] , [46] , [4] , [47] , [48] , [49 ] , [50 ] , [ 51 ], [52 ] , [24 ] , [37 ] , [42 ] 3. PKs and biodistribution…”
Section: The Auc Ratio -A Means To Assess An L-ldcmentioning
confidence: 99%
“…Another example of immediate cleavage was provided in a study with a methotrexate-based LDC conjugated to a dioleoylglyceride-anchor with a linker structure containing two ester and an amide bond (Fig. 2, compound 13) [46].…”
Section: In Vivo Drug Release Of Ldcsmentioning
confidence: 99%
See 1 more Smart Citation
“…В культуре RFC-дефицитных Т-лимфобластоидных клеток такие МТХ-липосомы преодолевали резистентность к МТХ [11]. В мышиной модели острого лейкемического варианта Т-клеточной лимфомы МТХлипосомы ингибировали рост опухоли эффективнее, чем интактный МТХ, и были менее токсичными [12].…”
unclassified